2020
DOI: 10.2337/dc19-0906
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoglycemia and Cognitive Function in Older Adults With Type 1 Diabetes: The Study of Longevity in Diabetes (SOLID)

Abstract: In children with type 1 diabetes (T1D), severe hypoglycemia (SH) is associated with poorer cognition, but the association of SH with cognitive function in late life is unknown. Given the increasing life expectancy in people with T1D, understanding the role of SH in brain health is crucial. RESEARCH DESIGN AND METHODS We examined the association between SH and cognitive function in 718 older adults with T1D from the Study of Longevity in Diabetes (SOLID). Subjects self-reported recent SH (previous 12 months) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 38 publications
6
52
0
2
Order By: Relevance
“…Details of participant eligibility and inclusion have been published previously and briefly presented in online supplemental figure 1. [16][17][18] Potential participants with T1D were identified in electronic medical records using International Classification of Diseases (ICD)-9 and ICD-10 codes for T1D (250.x1, 250.x3 or E10.x) or T2D (250.x0, 250.x2, E11.x). As per previous work using the SOLID dataset, [16][17][18] individuals with diagnostic codes related to both types of diabetes were classified as having T1D if at least 75% of diagnostic codes related to diabetes were for T1D specifically and the member was prescribed insulin to reduce the risk of misclassification.…”
Section: Study Populationmentioning
confidence: 99%
“…Details of participant eligibility and inclusion have been published previously and briefly presented in online supplemental figure 1. [16][17][18] Potential participants with T1D were identified in electronic medical records using International Classification of Diseases (ICD)-9 and ICD-10 codes for T1D (250.x1, 250.x3 or E10.x) or T2D (250.x0, 250.x2, E11.x). As per previous work using the SOLID dataset, [16][17][18] individuals with diagnostic codes related to both types of diabetes were classified as having T1D if at least 75% of diagnostic codes related to diabetes were for T1D specifically and the member was prescribed insulin to reduce the risk of misclassification.…”
Section: Study Populationmentioning
confidence: 99%
“…In adults data remain controversial, with consistently reassuring data coming from long-term follow-up of the DCCT/Epidemiology of Diabetes Interventions and Complications (EDIC) cohort of type 1 diabetes patients and from the Outcome Reduction With Initial Glargine Intervention (ORIGIN) trial in people with type 2 diabetes [ 57 , 58 ]. However, a recent large study in older adults with type 1 diabetes demonstrated an association between patient-reported history of severe hypoglycaemia events (episodes resulting in emergency department or inpatient admission), either recent (any) or life-time exposure, and impaired performance in global cognition, language and executive function and recent episodic memory, with evidence for a dose effect [ 59 ]. An earlier meta-analysis also found a bi-directional relationship between dementia and hypoglycaemia in older adults [ 60 ].…”
Section: The Cumulative Impact Of Hypoglycaemiamentioning
confidence: 99%
“…In this issue of Diabetes Care , complementary articles provide new insights into the consequences of severe hypoglycemia in older adults. Lacy et al ( 3 ) report that severe hypoglycemia is associated with reduced cognitive function in older adults with type 1 diabetes, and Standl et al ( 4 ) confirm the bidirectional nature of the association between severe hypoglycemia and cardiovascular (CV) events in adults with type 2 diabetes. Both investigations support reducing severe hypoglycemia as a clinical imperative in reducing diabetes-associated morbidity.…”
mentioning
confidence: 98%
“…In summary, these studies emphasize the need for glycemic treatment to move beyond glycemic control and include reduction of severe hypoglycemia, particularly in an older population with comorbidities. While Standl et al ( 4 ) clearly demonstrate a bidirectional relationship between severe hypoglycemia and CV events, Lacy et al ( 3 ) could not address the bidirectionality between severe hypoglycemia and impaired cognition because of the study’s cross-sectional design. Regardless, practitioners need to consider comorbidities such as frailty and cognitive dysfunction when making glycemic treatment recommendations for their patients with diabetes.…”
mentioning
confidence: 99%
See 1 more Smart Citation